Systematic review on the application of Virtual Reality in University Education - Caballero-Garriazo, Javier Alfredo (2023)
Introduction. Currently there are studies that explore benefits, impacts and applications of Virtual Reality (VR) and Augmented Reality (AR) in different technological and professional areas. It has sparked interest in research due to its enormous potential and its application at all levels of education. The periods of analysis of the Bibliographic information have been from 2010 to 2021 as a reference. Objective. Describe the application of VR and AR in the learning process in university education. Identify the thematic areas by determining the application domains in different areas. Methodology. Systematic mixed mapping was used. Documents indexed in digital libraries were reviewed. It was systematically filtered using keywords. Results. There are large gaps in the applications of VR, mainly in the areas of neuroscience and nursing (3%), however, there are greater studies in computer sciences (40%). Conclusion. The main findings have been that in Scopus in the period 2010 to 2021, the highest percentage of mentions about the application of VR by thematic areas and application domains has predominated. In the analysis it has been discovered that there are several gaps in the application of VR and in learning theories that have not considered the development of VR applications to help and guide towards learning results, they have only been for simulation and training.